Phytosociological Studies of the Monsoon Vegetation of Rocky Habitat - Gaur, Y. D.; Satyanarayan, Y. (Indian Forester, 1967)
Phytosociological studies of the monsoon vegetation of rocky habitat in arid zone were conducted at Kailana plateau. The vegetation and its environmental characters are discussed. Phytoaociologically the vegetation in summer is represented by dried plants of a permanent frame work, i.e,Aristida adsunsionis, Eleusine compressa, Lepidagathis trinervis and Tephrosia purpura which at the onset of rain sprout and are joined by numerous seedlings of annual and perennial plants. The density of annuals and perennials was highest during the middle of monsoon, after which it decreased gradually in perennials and sharply in annuals due to high mortality in the later. The mortality is governed by low moisture in top layers of soil and poor aggressiveness of the species.These factors are also responsible for the death of ephemerals which complete their life cycle within a short period. Except Oropetium thamaeum all the perennials showed continuous increase in their percentage Cover even up to the end of monsoon while annuals have highest percentage cover during the middle of monsoon only. Eleusine compressa is the most dominant species and seems to be the best grass for revegetating rocky habitat.